2020 42nd Annual International Conference of the IEEE Engineering in Medicine &Amp; Biology Society (EMBC) 2020
DOI: 10.1109/embc44109.2020.9176359
|View full text |Cite
|
Sign up to set email alerts
|

Towards Contactless Estimation of Electrodermal Activity Correlates

Abstract: This paper presents a proof-of-concept for contactless and nonintrusive estimation of electrodermal activity (EDA) correlates using a camera. RGB video of the palm under three different lighting conditions showed that for a suitably chosen illumination strategy the data from the camera is sufficient to estimate EDA correlates which agree with the measurements done using laboratory grade physiological sensors. The effects we see in the recorded video can be attributed to sweat gland activity, which inturn is kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…In the future, some of those limitations might be overcome by contactless methods. Besides imaging and analysis of skin surface temperature in the face, preliminary studies could show that the contactless approximation of EDA signal from RGB sensors on the hand is possible in a static lab setting [51]. The multimodal camera recordings of the face collected in this study can help to investigate whether noncontact monitoring methods are able to reliably approximate the temperature and EDA dynamics in the face to realize contactless real-time evaluation of MS.…”
Section: Discussionmentioning
confidence: 89%
“…In the future, some of those limitations might be overcome by contactless methods. Besides imaging and analysis of skin surface temperature in the face, preliminary studies could show that the contactless approximation of EDA signal from RGB sensors on the hand is possible in a static lab setting [51]. The multimodal camera recordings of the face collected in this study can help to investigate whether noncontact monitoring methods are able to reliably approximate the temperature and EDA dynamics in the face to realize contactless real-time evaluation of MS.…”
Section: Discussionmentioning
confidence: 89%
“…Previous research has shown that transient responses, which correlate with a person’s EDA signal, can be inferred from the periorbital, forehead, and maxillary regions of the face using thermal cameras [ 9 , 12 , 13 ]. Bhamboarae et al provided an early proof-of-concept that a person’s EDA can be inferred from the palm using an RGB camera by counting the specular reflections, which were created by specialized lighting conditions, on the palm [ 14 ]. Other research has shown that electrical stimulation and pain increase not only the sweat gland activity on the forehead but also increase the blood flow to the forehead (through sympathetic vasodilation) and the left cheek, and decreases the blood flow to the finger [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%